(untitled) (International Journal of Environmental Sciences, 2025)
Background:The present study involved the formulation design and modification of muco-adhesive tablet of isoniazid and fluoxetine. Isoniazid is a first line medication to treat tuberculosis but its efficacy is compromised by multi drug resistance. Its efficacy can be enhanced by combining it with fluoxetine, an antidepressant drug (selective serotonine reuptake inhibitor). One study reported in combination of fluoxetine with isoniazid reduce the MIC of isoniazid by 128th times. Furthermore, the effect of both drugs was sustained by formulating them in muco-adhesive tablet form. Methods: The mucoadhesive tablet was prepared by direct compression method and optmizwd by box behnken design. We used three levels to evaluate the effects of three independent variables—the concentrations of chitosan, microcrystalline cellulose (MCC), and HPMCK15M—on three dependent variables.Muco-adhesion strength, swelling index, and percentage of drug release at 20 hours were the dependent variables that were chosen in comparison to the independent factors. Results:The improved formulation F8 (180.71%) showed a high swelling index and a robust muco-adhesion strength of 45.87 grams. This formulation also exhibited a good % drug release(84.23%) at 20th hrs. The optimized formulation also exhibited the controlled drug release over 24 hrs as it follows the zero order drug release kinetics. Since there was no discernible change in the drug content over the course of 90 days, the stability experiments showed that all of the formulations were stable. Conclusion: According to these results, a good therapeutic delivery method for the successful treatment of gastric TB is the muco-adhesive tablet containing isoniazid and fluoxetine.